REMOÇÃO DE MATÉRIA ORGÂNICA CARBONÁCEA E NITROGENADA DE ESGOTO SANITÁRIO EM REATOR DE LEITO ESTRUTURADO COM AERAÇÃO INTERMITENTE - Leick, Sheilla Andrade (2016)
From the 90s, there was an increasing amount of resources invested in research, development and construction of wastewater treatment systems in order to reduce the amount of nutrients released into rivers. In Brazil, biological treatment systems used in part of the Effluent Treatment Plants (ETP), as Upflow Anaerobic Sludge Blanket (UASB) and activated sludge systems are effective in removing organic matter. However, they have limitations when the subject is considered the removal of nutrients such as nitrogen and phosphorus. Thus the present study was to evaluate the effectiveness of a structured bed reactor with intermittent aeration in removing organic matter and nitrogen from sewage. The hydraulic retention time (HRT) used was 12 hours, the temperature of 30 ± 1 ° C and the feed was continued. The reactor was operated for 339 days, during which were evaluated three different effluent recirculation flow, and 1Q 2Q 3Q and three different aeration times, where the reactor was aerated 1h, 2h, and 3h in 3 hours cycles, totaling 9 trials. It was in all tests performed Demand Chemical Oxygen removal (COD) and total nitrogen (TN) of at least 69.8% and 29.5%, respectively, and at most 89 , 2% and 55.5%, respectively. Statistical analysis showed no significant difference to the results of COD between tests. There was a strong positive correlation between denitrification and removal of NT, indicating that denitrification the limiting procedure. The lowest concentration of N-NH4, 3.1 mg.L-1, was achieved in Test 4, with recirculation of 2Q and aeration of 1h. In the same test the effluent COD was 40 mg.L-1. Analyzing the results we conclude that the structured bed reactor shows promise for concomitant removal of organic matter and total nitrogen.